Plädoyer zur gesetzlichen Regelung des Streikrechts – eine Replik - Thiess Büttner; Wolfram F. Richter; Horst Zimmermann (Wirtschaftsdienst, 2016)
In der Februarausgabe 2016 veröffentlichte der Wirtschaftsdienst den Aufsatz: "Streiks und die Zuverlässigkeit der Verkehrsbedienung" vom Wissenschaftlichen Beirat beim Bundesminister für Verkehr und digitale Infrastruktur. Dazu erscheint diese Replik. – – In the recent past, Germany has experienced increasing strike activity by small trade unions. This became possible through a change in high-level legislation allowing competition between trade unions at the firm level. The German government has responded by implementing a new law, which restricts this competition, but many observers regard it as inappropriate. In a recent issue of this journal, the Scientific Advisory Board to the Federal Ministry of Transport and Digital Infrastructure proposes specific legal measures to be taken. The present paper comments on these proposals. It supports the claim for legal regulation of strike activities, but it deviates with regard to the scope of application. The point is made that striking is an activity that inherently requires legal regulation, and that legal regulation is only dispensable in sectors governed by strong competition.
Keywords: J5; K31; 330; Arbeitskampf; Deutschland